Investigating the hygiene-related factors influencing prevalence of trachoma among children below nine years in Turkana West Sub-County, Turkana County, Kenya - Smalle Elimlim Duncan; Peter Edome Akwee; Paul L. Mutu (International Journal Of Community Medicine And Public Health, 2026)
Background: Turkana County is one of the counties where trachoma is endemic. Trachoma impact survey of 2024 indicated Turkana West Sub County having a prevalence of 11.8%. The purpose of the study is to investigate factors influencing prevalence of trachoma in children below nine years in Turkana West Sub County. The objective of the study includes investigating the hygiene related factors among children below nine years. Methods: The target population consisted of 23,493 households in wards in Turkana West Sub County. Stratified random sampling was used to obtain a sample of 223 households from all the wards in Turkana West Sub County. Purposive sampling was used to select 21 healthcare workers. Questionnaires and interview were used to collect data. University supervisors from Turkana University College assessed validity of the questionnaires. Piloting of the study was done in Loima Sub County. Data was presented using tables and graphs where frequencies and percentages were used to describe the data. Results: The findings revealed that presence of excess flies (47.3%), presence of human faeces (21.6%), sharing of clothing (45%) and poor facial hygiene (66.7%) contribute to trachoma transmission. Conclusions: These results underscore the urgent need for integrated public health interventions focused on improving sanitation, water access, and hygiene education to reduce trachoma prevalence and enhance child health in the region. The findings of this study help to reduce cases of trachoma in children below nine years. This study also benefit medical practitioners and other stakeholders for planning purposes.